The influence of metacognition and motivation on academic achievement among university students in Jordan - Al-Oqleh, Ahmad Mohammad
Metacognition and motivation play a vital role in increasing the level of academic achievement. Investigating the factors related to the low academic achievement of university students has become a topic of growing interested in higher education administrators and scholars in Jordan. Furthermore, it should be noted that metacognition is the most learned ability that influences the effectiveness of learning in terms of its inputs and outputs due to its essential role in the learning process. However, it is important to acknowledge that there are differences between low and high level motivations affecting academic achievement. Thus, higher education institutions in Jordan are experiencing challenges due to low rate academic achievement, especially among first-year university students. As such, this study attempts to identify the level of metacognition, motivation, and academic achievement, to identify the gender differences in meta cognition and motivation among the students as well as to identify the differences of students' academic achievement according to their meta cognition and level of motivation. This study also aims to measure the influence of metacognition and motivation on academic achievement. Finally, to examine which construct of metacognition and motivation are predictive of academic achievement. This quantitative study applied survey design using questionnaire as a data-gathering instrument. It used stratified random sampling technique involving 440 first-year university students. The data collected were analyzed using descriptive statistics (SPSS) to identify the student's level of metacognition, motivation, and academic achievement. In addition, the study uses inferential statistics (independent sample t- Test, ANOV A, and regression test) to identify the contnbution of metacognition and motivation on academic achievement. This study found that the level of metacognition and motivation among Jordanian public university students is moderate with majority of the students are within the pa level in academic achievement. The findings showed that there are significant differ nces based on gender where female students have higher level of metacognition and motivation compared to male students. The study also found that there are significant differences among the students in terms of metacognition and motivation where the students with high, medium and low levels in both aspects get high, moderate and low results in academic achievement, respectively. Metacognition and motivations have a significant contnbution on the students' academic achievement. The last finding is knowledge metacognition; regulation metacognition as well as intrinsic and extrinsic motivations are predictive of academic achievement. In this study, a new framework of metacognition and motivation on academic achievement has been developed. This study might be useful to the ministry of education and universities in Jordan in enhancing the students' academic achievement. It could also help to develop appropriate strategies that can cater for the students' needs and interests.